2019
DOI: 10.1080/26410397.2019.1581533
|View full text |Cite
|
Sign up to set email alerts
|

Critical insights on the demographic concept of “birth spacing”: locating Nef in family well-being, bodies, and relationships in Senegal

Abstract: Birth spacing has emerged since the early 1980s as a key concept to improve maternal and child health, triggering interest in birth spacing practices in low-income countries, and drawing attention to prevailing norms in favour of long birth intervals in West Africa. In Senegal, the Wolof concept of Nef, which means having children too closely spaced in time, is morally condemned and connotes a resulting series of negative implications for family well-being. While Nef and "birth spacing" intersect in key ways, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…Agreeing that contraception preserves a woman's beauty was positively related to adoption over the one-year period and, in communities where more women strongly agreed with this statement, women were less likely to discontinue. This supports findings from qualitative  Family Planning Beliefs and Their Association with Contraceptive Use Dynamics research showing that women reported using contraception for birth spacing to avoid distorting their bodies, postpone aging, and maintain strong, feminine bodies (Duclos et al 2019;Withers et al 2015;Kibira et al 2020). Additionally, qualitative studies among men have identified similar shared ideas, specifically that women who space their births by using contraception are healthier, stronger, and, therefore, more beautiful than women who do not use contraception and give birth more frequently (Withers et al 2015;Kibira et al 2020).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Agreeing that contraception preserves a woman's beauty was positively related to adoption over the one-year period and, in communities where more women strongly agreed with this statement, women were less likely to discontinue. This supports findings from qualitative  Family Planning Beliefs and Their Association with Contraceptive Use Dynamics research showing that women reported using contraception for birth spacing to avoid distorting their bodies, postpone aging, and maintain strong, feminine bodies (Duclos et al 2019;Withers et al 2015;Kibira et al 2020). Additionally, qualitative studies among men have identified similar shared ideas, specifically that women who space their births by using contraception are healthier, stronger, and, therefore, more beautiful than women who do not use contraception and give birth more frequently (Withers et al 2015;Kibira et al 2020).…”
Section: Discussionsupporting
confidence: 79%
“…This supports findings from qualitative research showing that women reported using contraception for birth spacing to avoid distorting their bodies, postpone aging, and maintain strong, feminine bodies (Duclos et al. 2019 ; Withers et al. 2015 ; Kibira et al.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…South Sudan committed in 2017 to increase contraceptive prevalence to 10% by 2020 (Government of South Sudan, 2017), and reducing unmet need for contraception is a specific objective in its 2019-2029 Reproductive Health Policy. One way to frame the discussion, as recommended in a 2011 study in South Sudan (Pillsbury et al, 2011) and by South Sudanese colleagues during the authors' dissemination of these results in Juba, is with the positive effect of birth spacing on women's and children's health and survival, an appropriate strategy in places where contraception may be sensitive (Duclos et al, 2019;Kane et al, 2016;Post, n.d.), or where post-partum sexual abstinence is traditionally practiced (Pillsbury et al, 2011). It is important that a range of short-and long-acting contraceptive methods be made available at no cost and provided by well-trained staff in a private location.…”
Section: Discussionmentioning
confidence: 99%